Does urban mixed use development approach explain spatial analysis of inner city decay? - Rasoul Farjam; Maliheh Hossieni Motlaq (Journal of Urban Management, 2019)
Generally speaking, population and activities have long been associated with central part of cities. This pattern with its special structure has exemplified itself in specific functional patterns followed by accommodation of mix urban land uses. Residences could recreate as well as having civilized interactions. It is been argued that the historical trend pertaining to moving away or abandoning inner city activities toward periphery followed by formation of sprawl development as well as changes in central city land uses have great impact upon urban areas status. It may result in social, economic and physical urban deterioration and decay. From urban planning policies and systems standpoints, inner city decay is associated with urban land use zoning as well as geometric typology pertaining to rationalism philosophy and modernism planning. It is argued that social, economic and physical properties associated with urban land uses including the existence of pedestrian areas, varied land uses and social spaces no longer apply to central part of the city taking into account this type of philosophy. This study deals with the central part of Shiraz. It aims to explain the relationship between urban developments based on mix used development and degree of urban deterioration and decay as opposed to urban efficiency. It further identifies indices and components associated with the spatial analysis of inner city decay as opposed to urban land uses efficiency. The methodological procedure of this study is based on functional spatial analysis using new urbanism paradigm with particular emphasis on urban mixed land uses. This Study suggests that there exist a negative linear relationship between urban land uses located in central Part of Shiraz and degree of inner city deterioration and decay level. It further suggests that urban inner city decay in Shiraz follows a specific spatial behavior both at district and neighborhood levels.
Keywords: 710; Inner-city decay; New urbanism; Shiraz metropolitan; Spatial analysis of inner city decay; Urban land use efficiency; Urban mixed use development